Proposta colaborativa para elaboração de um plano de ação embasado no currículo funcional natural em um hospital de retaguarda - Rossini, Maria Gabriella (Universidade Federal de São Carlos, 2025)
The Natural Functional Curriculum proposes teaching methods centered on the learning of adaptive skills in real-life contexts, with a focus on autonomy and functionality, and is widely used in Special Education. This study aimed to develop and evaluate an action plan based on this curriculum for a patient with cerebral palsy, through collaborative work among hospital professionals. It is a descriptive, qualitative, and collaborative study conducted in a long-term care hospital in the interior of São Paulo, which serves patients full-time with high levels of dependency and clinical complexity. Five members of the multidisciplinary team and one adult patient, institutionalized for approximately forty years, participated in the study. Data collection was carried out through interviews, observation of the hospital routine, and individual meetings with professionals for the construction of the action plan. After data collection, the plan was evaluated by the team, by a hospital manager, and presented to the patient, who also contributed suggestions. The resulting plan was described as a document that includes objectives, goals, strategies, methods for implementing interventions, resources, and evaluation criteria. The professionals highlighted the practical applicability of the proposal within the hospital routine, with the potential for extension to other patients. It is concluded that the development of an action plan based on the Natural Functional Curriculum, with the active participation of the multidisciplinary team and patient-centered focus, contributes to the effectiveness of interventions and the promotion of socio-emotional skills in the hospital setting.
Collaborative proposal for developing an action plan based on the natural functional curriculum in a long-term care hospital
Keywords: Educação especial; Currículo funcional natural; Paralisia cerebral; Hospital de retaguarda; Equipe multiprofissional; Special education; Natural functional curriculum; Cerebral palsy; Long-term care hospital; Multidisciplinary team; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; CIENCIAS HUMANAS::EDUCACAO